THE ANGIOGENESIS ACTIVITIES OF GEL CACAO SEED EXTRACT ON GUM INCISION WOUND HEALING IN GUINEA PIGS - Kusmayani, Ketut Novi; Warditha, Anak Agung Gde Jaya; Berata, I Ketut (Buletin Veteriner Udayana, 2022)
One of alternative herbal therapy ingredients, cocoa beans because it contains flavonoids, polyphenols, and alkaloids can reduce number of macrophages and antioxidants, to accelerate inflammatory process. This study was aimed determine effect cocoa bean extract gel on healing guinea pig gum incisions based on level angiogenesis. This study was experimental study using completely randomized design, with four treatments with 6 replications, total of 24 experimental animals. Guinea pigs were injected with ketamine at dose of 50 mg/kg BW anesthetic, then incision made in gums with length 10 mm and depth 2 mm. Then given treatment of topical cocoa bean extract gel, (T 0 ) group with concentration 0%, (T 1 ) 16%, (T 2 ) 24%, (T 3 ) 32%, each for 5 days. On 6th day euthanasia was performed and gum tissue was taken. Gum tissue was processed preparation of histology preparations using Hematoxylin-Eosin (HE) staining method. Histopathological examination preparations were carried out with a microscope based on level angiogenesis. Results of histopathological examination obtained an average level angiogenesis at To=19.00, T1=38.00, T2=43.50, T3=47.83. Statistical analysis showed that there was a significant increase in angiogenesis between controls (T0) compared to group given cocoa bean extract gel (T1, T2 and T3). But between treatment groups T1, T2 and T3 there was no significant difference. It can conclude topical application of cocoa bean extract gel has been shown increase angiogenesis in guinea pig gum incision wound healing. Administration of cocoa bean extract with a concentration of 32% resulted in highest angiogenesis rate.